Lo spazio e il tempo nella costruzione dell’Europa - Melchionni, Maria Grazia (Rivista di studi politici internazionali, 2022)
The article describes the originality of the European integration process and recounts, rapidly, its evolution on the base of the main coordinates of international life: space and time. Progressive transition from Little Europe to enlarged Europe, to Paneurope and, at the same time, from Cold War to détente, to globalization represents, therefore, the reading-key of the European design’s evolution in all its aspects: political, institutional, economic, social and cultural. The Author underlines the ‘plural’ character of political identity already achieved by the European Union and the need to enhance its security identity facing up to contemporary challenges. Today the project of a European Federation looks expired and other plans for Europe need to be shaped up, considering its inside diversities and how more complex international relations are in the globalization’s context.